Logistical Facilitators and Barriers to PrEP Implementation in Methadone Clinic Settings: Provider and Staff Perspectives. Issue 5 (14th September 2022) - Jaiswal, Jessica; Griffin, Marybec; Hascher, Kevin; Cox, Amanda B.; Dunlap, Kandyce; Walters, Suzan; LoSchiavo, Caleb; Burton, Wanda M.; Mumba, Mercy
Abstract : Objectives: The purpose of this study was to examine the feasibility of implementing pre-exposure prophylaxis (PrEP), a daily oral medication for human immunodeficiency virus (HIV) prevention, in methadone clinics. Methods: Medical and nonmedical staff (n = 30) at 2 methadone clinics in Northern New Jersey were qualitatively interviewed about various aspects of substance use treatment, clinical operations, and HIV risk and prevention among their patient populations. Audio-recorded interviews were professionally transcribed, then coded and analyzed by the research team. Results: Themes surrounding the viability of PrEP implementation emerged for both logistical facilitators and barriers. Facilitators included availability of prescribing clinicians, ability to conduct lab testing on-site, and availability of existing hepatitis C programs as a blueprint for PrEP management. Barriers included increased provider burden, financial concerns, and perceptions that PrEP provision is outside the clinic's treatment scope. Conclusions: Although staff expressed willingness and potential ability to provide PrEP, they identified barriers regarding insurance reimbursement, limited funding, and concerns that PrEP would extend the clinic's treatment scope. However, given the enabling factors such as availability of providers and existing clinical infrastructure, providing PrEP could increase clinic revenue through insurance reimbursement and federal funding for PrEP-related services. Clinic-level education is needed for clinical and nonclinical staff to better understand the logistics of implementing PrEP, particularly regarding prescribing practices, billing and insurance concerns, and the essential nature of HIV prevention as a critical component of substance use treatment.